Evaluation of tactile sensors as an alternative to force sensors in an assistive haptic handlebar - Trujillo-León, Andrés; Bachta, Wael; Vidal-Verdú, Fernando (IEEE, 2017)
This paper shows experimental results that confirm that tactile sensors are appropriate to provide information about the caregiver intention in an assistive haptic handlebar. Preliminary tests have been performed to identify possible control inputs. Specifically, experiments have been carried out with a rear handlebar that incorporates tactile sensors and a force/torque sensor mounted on a powered wheelchair. An overall strong correlation is found between variables obtained from the tactile sensors output and those from the force/torque sensor that model the user interaction during driving. This way, an intuitive and easy driving can be achieved with a handlebar based exclusively on tactile sensors, which are a cost-effective alternative to force sensors.
Keywords: Tecnología de la rehabilitación; Force; Wheelchairs; Tactile sensors; Force sensors; Correlation; Torque